Should we “eliminate” PDA shunt in preterm infants? A narrative review - Surak, Aimann; Sidhu, Amneet; Ting, Joseph Y. (Frontiers in Pediatrics, 2024)
The patent ductus arteriosus frequently poses a significant morbidity in preterm infants, subjecting their immature pulmonary vascular bed to substantial volume overload. This, in turn, results in concurrent hypoperfusion to post-ductal organs, and subsequently alters cerebral blood flow. In addition, treatment has not demonstrated definitive improvements in patient outcomes. Currently, the optimal approach remains a subject of considerable debate with ongoing research controversy regarding the best approach. This article provides a comprehensive review of existing literature.